Minimising risk of cardiovascular drug interactions with statins. Issue 8 (15th September 2021) - Thompson, Angus
Abstract : There are several medications used in the management of cardiovascular disease that can interact with statins, and these drugs are very likely to be indicated in patients who are also prescribed a statin. This article discusses what prescribers and pharmacists can do to minimise the risk of harm from these potential interactions.